Early and Long-Term Follow-Up for Chronic Type B and Type Non-A Non-B Aortic Dissection Using the Frozen Elephant Trunk Technique - Luo, Congcong; Qi, Ruidong; Zhong, Yongliang; Chen, Suwei; Liu, Hao; Guo, Rutao; Ge, Yipeng; Sun, Lizhong; Zhu, Junming (Frontiers in Cardiovascular Medicine, 2021)
Background: This study aimed to evaluate the early and long-term outcomes of a single center using a frozen elephant trunk (FET) procedure for chronic type B or non-A non-B aortic dissection. Methods: From February 2009 to December 2019, 79 patients diagnosed with chronic type B or non-A non-B aortic dissection who underwent the FET procedure were included in the present study. We analyzed operation mortality and early and long-term outcomes, including complications, survival and interventions. Results: The operation mortality rate was 5.1% (4/79). Spinal cord injury occurred in 3.8% (3/79), stroke in 2.5% (2/79), and acute renal failure in 5.1% (4/79). The median follow-up time was 53 months. The overall survival rates were 96.2%, 92.3%, 88.0%, 79.8%, and 76.2% at 1/2, 1, 3, 5 and 7 years, respectively. Moreover, 79.3% of patients did not require distal aortic reintervention at 7 years. The overall survival in the subacute group was superior to that in the chronic group (P=0.047). Conclusion: The FET technique is a safe and feasible approach for treating chronic type B and non-A non-B aortic dissection in patients who have contraindications for primary endovascular aortic repair. The technique combines the advantages of both open surgical repair and endovascular intervention, providing comparable early and long-term follow-up outcomes and freedom from reintervention.